Endonuclease from Micrococcus luteus Which Has Activity Toward Ultraviolet-Irradiated Deoxyribonucleic Acid: Its Action on Transforming Deoxyribonucleic Acid - Setlow, R. B. (1970)
An endonuclease purified from Micrococcus luteus makes single-strand breaks in ultraviolet (UV)-irradiated, native deoxyribonucleic acid (DNA). The purified endonuclease is able to reactivate UV-inactivated transforming DNA of Haemophilus influenzae, especially when the DNA is assayed on a UV-sensitive mutant of H. influenzae. After extensive endonuclease action, there is a loss of transforming DNA when assayed on both UV-sensitive and -resistant cells. The endonuclease does not affect unirradiated DNA. The results indicate that the endonuclease function is involved in the repair of biological damage resulting from UV irradiation and that the UV-sensitive mutant is deficient in this step. We interpret the data as indicating that the various steps in the repair of DNA must be well coordinated if repair is to be effective.